Genome-wide association study and targeted metabolomics identifies sex-specific association of CPS1 with coronary artery disease - Jaana A. Hartiala (Nature Portfolio, 2016)
Dietary choline metabolites, such as trimethylamine N-oxide and betaine, have been associated with coronary artery disease (CAD). Here, Hartiala et al. identify two genetic loci for betaine levels on chromosomes 2q34 and 5q14.1 and find that the 2q34 locus was also associated with other pathway intermediates, and decreased risk of CAD in women.